Infusions and Fumigations: Literacy Ideologies and Therapeutic Aspects of the Qurʾan. Issue 1 (3rd July 2017) - Wilkens, Katharina
Abstract : Written texts, especially sacred texts, can be handled in different ways. They can be read for semantic content; or they can be materially experienced, touched, or even be inhaled or drunk. I argue that literacy ideologies regulate social acceptability of specific semantic and somatic text practices. Drinking or fumigating the Qurʾan as a medical procedure is a highly contested literacy event in which two different ideologies are drawn upon simultaneously. I employ the linguistic model of codeswitching to highlight central aspects of this event: a more somatic ideology of literacy enables the link to medicine, while a more semantic ideology connects the practice to theological discourses on the sacredness of the Qurʾan as well as to the tradition of Prophetic medicine. Opposition to and ridicule of the practice, however, comes from representatives of an ideology of semantic purity, including some Islamic theologians and most Western scholars of Islam. Qurʾanic potions thus constitute an ideal point of entry for analyzing different types of literacy ideologies being followed in religious traditions.